Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let $f: S^{-1} M \to S^{-1}A \otimes_A M$ defined by $$m/s \to 1/s \otimes m$$ $g: S^{-1}A \otimes_A M \to S^{-1} M$ defined by $$a/s \otimes m \to am/s $$

Prove that $f$ and $g$ are well defined ?

how can we prove f is S-1A mod homom ?

Here $A$ is commutative ring with identity and $M$ is module and $S$ multiplicative subset of $A$.

share|improve this question
    
You mean $S$ is a multiplicative subset of $A$ ? –  user18119 Nov 18 '12 at 19:57
    
yes sorry thats what i meant –  user48931 Nov 18 '12 at 20:05
    
the only problem I have is how to prove that f is well defined ? all the rest is ok –  user48931 Nov 18 '12 at 20:39
add comment

3 Answers

Hint: To get the map $S^{-1}A \otimes_A M \rightarrow M$, define a suitable bilinear map $S^{-1}A \times M \rightarrow S^{-1}M$ and then use the universal property of the tensor product.

To show that the map $S^{-1}M \rightarrow S^{-1}A\otimes_A M$ is well defined, note that $m/s = n/t \Rightarrow \exists s' \in S| s'(tm - sn) = 0 \Rightarrow (1/s'st) \otimes (s'(tm - sn)) = 0 \Rightarrow (1/st) \otimes (tm - sn) = 0 \Rightarrow (1/s) \otimes m - (1/t) \otimes n = 0$

share|improve this answer
    
got it thanks :) –  user48931 Nov 18 '12 at 20:59
add comment

To prove that the maps are well-defined, you must show that if $m/s=m^\prime/s^\prime$, then $f(m/s)=f(m^\prime/s^\prime)$. For $f$, this means that you must show that $1/s^\prime \otimes m^\prime = 1/s \otimes m$. This follows from the following fact: $(ms^\prime-m^\prime)r=0$ for some $r \in A$. Now, multiply both sides of $1/s^\prime \otimes m^\prime = 1/s \otimes m$ with $ss^\prime$, and use that (since we tensor over $A$), you can move elements from $A$ on the other side of $\otimes$). Multiply on both sides by $r$. The result follows.

To prove that $g\circ f$ is the identity, just plug in and see what happens. A general element in $S^{-1}M$ is written as $m/s$. Now: $g(f(m/s))=g(1/s \otimes m)=m/s$, so $g \circ f$ is the identity. The composition $f \circ g$ is similar.

share|improve this answer
    
how can we prove f is S-1A mod homom ? –  user48931 Nov 18 '12 at 21:00
    
@user48931: That just means that $f$ is a homomorphism of abelian groups plus it preserves the $S^{-1}A$-module structure: $f(am/s)=(a/s)f(m)$. That can be checked. –  Fredrik Meyer Nov 18 '12 at 21:12
    
dont we have to prove that f(a'/s' . m/s ) = a'/s' f(m/s) ? –  user48931 Nov 18 '12 at 21:16
    
@user48931: That amounts to the same thing, because $f((a^\prime/s^\prime) m/s)=f((a/ss^\prime)m)$. –  Fredrik Meyer Nov 18 '12 at 21:23
    
Then we have to prove f(am/s) = a f (m/s) right ? –  user48931 Nov 18 '12 at 21:31
show 4 more comments

Prove that $f$ is well defined

means the following:

An element of $S^{-1}M$ is an equivalence class of "fractions" $m/s$. Prove that $f(m/s)$ remains the same no matter what representative for the equivalence class of $m/s$ you choose.

(This is more or less always what it means when an exercise tells you to prove that a function is well-defined.) So, two fractions $m/s$ and $n/t$ represent the same equivalence class if there is an $u\in S$ such that $u(tm - sn) = 0$. So, let's see what happens to the two fractions if we use $f$ on them: $$ f(m/s) = 1/s \otimes m \\ f(n/t) = 1/t\otimes n $$ Now, the question is, do they represent the same element in $S^{-1}A \otimes_A M$? The usual way to test this is to take the difference between the two results and verify that it equals $0$. But as they stand it's not easy to calculate the difference, since the two tensor products have no terms in common. We need to fix that.

In $S^{-1}A$, we have that $1/s = ut/ust$, and likewise, $1/t = us/ust$, so we get (by bilinearity of tensor product): $$ 1/s \otimes m = ut/ust \otimes m = 1/ust\otimes utm \\ 1/t \otimes n = us/ust \otimes n = 1/ust\otimes usn $$ Now we can calculate the difference between these two as $$ 1/ust\otimes utm - 1/ust\otimes usn = 1/ust\otimes (utm - usn) = 1/ust\otimes 0 = 0 $$ and thus the value of $f$ at $m/s$ in independent of the choice of representative, and $f$ is therefore well defined. Can you make a similar reasoning for $g$? Can you prove that $f\circ g$ and $g\circ f$ are the identity functions on their respective $A$-modules? What does this tell us about the relationship between $S^{-1}A \otimes_A M$ and $S^{-1}M$?

share|improve this answer
    
Thanks for the help , Yes I proved that f 0g and g 0 f are identity and that means that S−1A⊗AM and S−1M are isomorphic to each others –  user48931 Nov 18 '12 at 20:48
    
how can we prove f is S-1A mod homom ? –  user48931 Nov 18 '12 at 21:01
    
Well, by definition, a group homomorphism $h:N\to N'$ of modules over a ring $R$ is an $R$-module homomorphism if $$ h(rm) = rh(m) $$ for any $r \in R$ and $m \in N$ (the fact that $h$ is a group homomorphism covers the case $r = 1$, if such an element exists in $R$). Since in this case, $h = f$, $R = S^{-1}A$, $N = S^{-1}M$ and $N' = S^{-1}A\otimes M$, you have to rewrite $r$ and $m$ as fractions, calculate, and see what you get on each side of the equality sign. If they turn out to be equal, then you have a module homomorphism. –  Arthur Nov 18 '12 at 22:04
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.